Depressive and Anxiety Symptoms Predict Sustained Quality of Life Deficits in HIV-Positive Ugandan Adults Despite Antiretroviral Therapy - Ezeamama, Amara E.; Woolfork, Makhabele N.; Guwatudde, David; Bagenda, Danstan; Manabe, Yukari C.; Fawzi, Wafaie W.; Fawzi, Mary C. Smith (Medicine, 2016)
: The impact of psychosocial status at onset of antiretroviral therapy on changes in quality of life (QOL) and subjectively rated health (SRH) among adults on ART in resource-limited settings is poorly understood. Therefore, we evaluate the association between stigma, anxiety, depression, and social support and change in QOL and SRH in HIV-infected Ugandan adults during an 18-month period. Psychosocial indicators were assessed at enrollment using structured questionnaires. QOL and SRH measures were assessed at months 0, 6, 12, and 18 using the Medical Outcomes Survey-HIV. Linear mixed models determined risk estimated differences in QOL and SRH in relation to quartiles of each psychosocial status indicator. Repeated measures generalized estimating equations modeling was implemented to assess differences inlikelihood ofimproved versus nonimproved SRH during follow-up. QOL scores and SRH improved significantly for all participants over 18 months (P< 0.0001). The gain in QOL increased dose-dependently as baseline depressive symptoms (time depression P< 0.001) and anxiety levels (time anxiety P< 0.001) declined. Lower social support was associated with worse QOL at baseline (P¼ 0.0005) but QOL improvement during follow-up was not dependent on baseline level of social support (time social support P¼ 0.8943) or number of stigmatizing experiences (time stigma P¼ 0.8662). Psychosocial determinants did not predict changes in SRH in this study. High levels of depression and anxiety symptoms at HAART initiation predicts lower gains in QOL for HIV-positive patients for as long as 18 months. Long-term QOL improvements in HIV-infected adults may be enhanced by implementation of psychosocial interventions to reduce depression and anxiety in HIV-infected adults
Keywords: Anxiety Symptoms; Quality; Life Deficits; HIV-Positive Ugandan Adults; Antiretroviral Therapy